Male-linked gene TsRPL10a′ in androdioecious tree Tapiscia sinensis: implications for sex differentiation by influencing gynoecium development. (19th November 2022) - Wang, Feng; Ren, Xiaolong; Jiang, Minggao; Hou, Kunpeng; Xin, Guiliang; Yan, Feng; Zhao, Peng; Liu, Wenzhe
Abstract: The mechanism of sex differentiation in androdioecy is of great significance for illuminating the origin and evolution of dioecy. Tapiscia sinensis Oliv. is a functionally androdioecious species with both male and hermaphroditic individuals. Male flowers of T. sinensis lack the ovules of gynoecia compared with hermaphrodites. To identify sex simply and accurately, and further find the potential determinants of sex differentiation in T. sinensis, we found that TsRPL10a′, a duplicate of TsRPL10a, was a male-linked gene. The promoter (5′ untranslated region and the first intron) of TsRPL10a′ can be used to accurately identify sex in T. sinensis . TsRPL10a is a ribosomal protein that is involved in gynoecium development, and sufficient ribosomal levels are necessary for female gametogenesis. The expression level of TsRPL10a was significantly downregulated in male flower primordia compared with hermaphrodites. The RNA fluorescence in situ hybridization (FISH) assay demonstrated that TsRPL10a was almost undetectable in male gynoecia at the gynoecial ridge stage, which was a key period of ovule formation by scanning electron microscope observation. In male flowers, although the promoter activity of TsRPL10a was significantly higher than TsRPL10a′ verified by transgenic Arabidopsis thaliana, the transcriptional expression ratio of TsRPL10a was obviously lower than TsRPL10a′ and reached its lowest at the gynoecial ridge stage, indicating the existence of a female suppressor. The promoter similarity of TsRPL10a and TsRPL10a′ was only 45.29%; the genomic sequence similarity was 89.8%; four amino acids were altered in TsRPL10a′ . The secondary structure of TsRPL10a′ was different from TsRPL10a, and TsRPL10a′ did not exhibit FISH and GUS expression in the gynoecium the way TsRPL10a did. From the perspective of RT-qPCR, its high expression level, followed by the low expression level of TsRPL10a in male flowers, indicates its antagonism function with TsRPL10a . The evolutionary analysis, subcellular localization and flower expression pattern suggested that TsRPL10a might be functionally conserved with AtRPL10aA, AtRPL10aB and AtRPL10aC in A. thaliana . Overall, we speculated that TsRPL10a and its duplicate TsRPL10a′ might be involved in sex differentiation by influencing gynoecium development in T. sinensis .